Laju Nitrifikasi pada Bioremediasi Air Limbah Organik Menggunakan Chlorella sp. dan Bakteri Nitrifikasi-Denitrifikasi - Arya Ksatria Fernanda Hendrawan; Norma Afiati; Arif Rahman (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2021)
Global nitrogen pollution in the aquatic environment has been increased mostly due to the disposal of organic wastewater from human activities. Chronic disposal of nitrogen compounds into the waters causes eutrophication and death of aquatic organisms. Process of reducing nitrogen in wastewater can be carried out economically and efficiently using nitrifying-denitrifying bacteria. Beside that, another environmentally friendly technology that can also be used is bioremediation using microalgae such as Chlorella sp. The synergistic relationship between bacteria and microalgae has a potential to better reduce performance of nitrogen compounds in organic wastewater. This study, which was conducted from July to August 2020, was laboratory experiment using randomised block design. It aimed to determine growth rate of Chlorella sp., rate of nitrification, rate of changes of nitrate compounds, effect of differences between treatments and duration of the changes of nitrate levels in organic wastewater as also relationship between Chlorella sp. to the nitrifying-denitrifying bacteria. Fresh wastewater samples were taken from Lake Rawa Pening. The results showed that growth pattern of Chlorella sp. has increased until the peak day (day 6) then decreased toward day 9. The highest nitrification rate was performed by treatment C, i.e., 0.2 mg NH4-N.l-1.hour-1 followed by treatment B, D and A respectively, 0.169, 0.009 and 0.008 mg NH4-N.l-1.hour-1. Similarly, the highest percentage change in nitrate compounds during the study was treatment C (1874%), B (1664%), D (200%) and A (175%) subsequently. The analysis of variance between treatment for changes in nitrate compounds was significantly different (p value <0.05). A further DMRT/Duncan Multiple Range Test showed that the highest average was also treatment C, B, D and A.